Relationship Between Aneurysm Volume and Histologic Healing after Coil Embolization in Elastase-Induced Aneurysms: A Retrospective Study - Ding, Y.H.; Dai, D.; Kadirvel, R.; Lewis, D.A.; Cloft, H.J.; Kallmes, D.F. (American Journal of Neuroradiology, 2008)
BACKGROUND AND PURPOSE: There are, to our knowledge, no histologic data correlating aneurysm volume with histologic healing following coil embolization of aneurysms. We report a retrospective study comparing histologic outcome with aneurysm volume in elastase-induced aneurysms in rabbits.MATERIALS AND METHODS: Aneurysm volume and histologic healing after coil embolization were retrospectively analyzed in 37 elastase-induced aneurysms in rabbits. Aneurysm dimensions (including neck, width, height, and volume) were measured and calculated. Packing density (PD) was calculated. Angiographic results were evaluated as recurrence, stable, and progressive occlusion. An ordinal grading system was used to evaluate the histologic healing after embolization. Correlations among aneurysm volume, PD, and histologic healing were analyzed by conducting linear regression analysis.RESULTS: For all the aneurysms in this study, mean aneurysm volume was 80.8 ± 48.6 mm3 (from 22 to 192 mm3), mean PD was 30.4 ± 8.3% (from 17% to 49%), and mean histologic score was 6.1 ± 2.0 (from 0.5 to 9.5), respectively. Correlations between aneurysm volume and PD, aneurysm volume and histologic healing, and aneurysm packing and histologic healing were all significant (P < .01).CONCLUSION: In this study, aneurysms with smaller volumes and higher PD were associated with the most complete histologic healing. The incomplete healing seen in the larger aneurysms is consistent with the higher incidence of recurrences after endovascular treatment that is seen in large human aneurysms.